THE ROLE OF THE CONCEPT OF "STEP" IN LANGUAGE AND CULTURE: A LINGUOPRAGMATIC ANALYSIS IN UZBEK AND ENGLISH - Qayumova Mohinur Murodullayevna (Western European Studies, 2024)
This article studies the concept of “step” from a linguistic and cognitive perspective. The concept of stepfather is analyzed in the context of the Uzbek national mentality and worldview, revealing its lexical, connotative and etymological features. The development of the conceptual system, its formation in the human mind and its relationship with other concepts are explained. The article emphasizes the national identity of the word “step” and conducts a comparative analysis of it with its equivalents in other languages. The cultural, social and linguistic aspects of this concept are also analyzed
Keywords: Step; concept; conceptual system; Uzbek language